THE MEDIATING EFFECT OF BRAND LOVE ON BRAND TRUST AND BRAND LOYALTY: CONCEPTUAL PAPER - Aimi Nadia Ibrahim; Noor Hasmini Abd Ghani (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Brand loyalty is the optimistic association consumers attach to a particular product or brand. Customers who exhibit brand loyalty are devoted to a product or service, demonstrated by their repeat purchases despite competitors’ efforts to lure them away. Based on Dick and Basu’s customer loyalty model, this paper proposes a conceptual framework for brand trust, brand love, and brand loyalty. Brand trust and brand loyalty have been widely discussed. However, some research on brand trust has modeled trust as an outcome, mediator, or moderator, and very few studies have modeled trust as the main predictor of brand loyalty. Therefore, trust as a predictor is introduced in the conceptual framework to determine if a positive behavioral outcome exists. Given that it is important, the study examined the effect of brand trust on brand loyalty. This study predicts that brand trust has a positive on brand loyalty. The mediating effect of brand love has mediated the relationship between brand trust and brand loyalty.